Single visit custom made flexible feeding obturator for an infant with tetralogy of fallot - Manu Rathee; Amit K Tamrakar (Saudi Journal of Medicine and Medical Sciences, 2015)
Cleft lip and palate prevalence is more in patients with heart diseases than in patients with normal hearts. The co-existence of tetralogy of Fallot and cleft palate undermines the health of the infant by underfeeding and circulation of low arterial oxygen concentration. Early prosthodontic adjuvant therapy with feeding obturator is mandatory for rehabilitation till corrective surgery.